2022
DOI: 10.3390/nu14061256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Moderate Caloric Restriction on the Reproductive Function in Aged Male Wistar Rats

Abstract: Caloric restriction (CR) has been shown to be an effective nutritional intervention for increasing longevity in some animal species. The objective of this study was to evaluate CR’s effects on metabolic and reproductive parameters in 12-month-old male Wistar rats. The rats were distributed in three groups: control, CR at 15%, and CR at 35% for 6 (up to 18 months of age) and 12 months (up to 24 months of age). At the end of CR treatment, we evaluated reproductive (male sexual behavior (MSB), sperm quality) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Comparatively, the mice in previous studies were around 4 – 6 months of age on their last MSB test (David, Wyrosdic, & Park, 2022; David, Wyrosdic, Wan, et al ., 2022). This is a potential confound as ageing is known to impair MSB (Wilson et al ., 2018; Jesús et al ., 2022). Future studies could independently test these variables (i.e social isolation, social exposure, and ageing) to determine how each may contribute to the altered percentage of SI persistent maters.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, the mice in previous studies were around 4 – 6 months of age on their last MSB test (David, Wyrosdic, & Park, 2022; David, Wyrosdic, Wan, et al ., 2022). This is a potential confound as ageing is known to impair MSB (Wilson et al ., 2018; Jesús et al ., 2022). Future studies could independently test these variables (i.e social isolation, social exposure, and ageing) to determine how each may contribute to the altered percentage of SI persistent maters.…”
Section: Discussionmentioning
confidence: 99%
“…High-calorie diets generally have negative effects on male fertility (e.g. Rato et al (2014)), whereas the effects of dietary restriction on male fertility and reproduction vary: Dietary restriction had a negative effect on sperm count, sperm motility and capacitation ability in young 2-month-old Sprague-Dawley rats (Rattus norvegicus) (Li et al, 2021), but had no effects on ejaculate quality in 2.5-month-old rats that were also exposed to heat stress (Aydilek et al, 2015) and led to a positive effect on ejaculate quality in aged 12-month-old Wistar rats (Jesús et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Rato et al. (2014)), whereas the effects of dietary restriction on male fertility and reproduction vary: Dietary restriction had a negative effect on sperm count, sperm motility and capacitation ability in young 2‐month‐old Sprague–Dawley rats ( Rattus norvegicus ) (Li et al., 2021), but had no effects on ejaculate quality in 2.5‐month‐old rats that were also exposed to heat stress (Aydilek et al., 2015) and led to a positive effect on ejaculate quality in aged 12‐month‐old Wistar rats (Jesús et al., 2022). A randomised trial of dietary restriction in obese men showed an increase in sperm count and sperm concentration in the trial group under caloric restriction (Andersen et al., 2022), whereas a systematic meta‐analysis on the impact of dietary manipulation on sperm has reported that food reduction led to alterations in ejaculate traits in mammals, arthropods and fish, but the extension of the effects varied across taxa (Macartney et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary restriction had a negative effect on sperm count and sperm motility and capacitation ability in young two-months old Sprague Dawley rats (Li et al, 2021). However, it had no effects on 2.5-months old Sprague Dawley rats that were also exposed to heat stress (Aydilek et al, 2015) or led to a positive effect in aged 12-months old Wistar rats (Jesús et al, 2022). A randomised trial of dietary restriction in obese men showed an increase in sperm count and sperm concentration in the trial group under caloric restriction (Andersen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%